ENHANCING TEACHER PERFORMANCE: THE IMPACT OF WORK MOTIVATION, TEACHER COMPETENCE, AND ORGANIZATIONAL CULTURE WITH TRANSFORMATIONAL LEADERSHIP AS A MODERATOR - Maria Dolora Biabi; Ellisa F. Laili; Elevenson Nadapdap; Rudy Wahyono; Pudjo Sugito (Adisam Publisher, 2025)
This study examines the impact of work motivation, teacher competence, and organizational culture on teacher performance, with transformational leadership as a moderating variable. The findings reveal that work motivation and teacher competence significantly enhance teacher performance, while work culture also plays a crucial role in shaping a productive educational environment. Moreover, transformational leadership strengthens the effects of motivation and competence, highlighting its importance in fostering high-performing educators. However, its moderating role in the work culture–performance relationship is less pronounced, suggesting that work culture independently influences teacher effectiveness. These findings contribute to existing theoretical frameworks by integrating motivation, competence, and work culture with leadership dynamics, offering insights into how leadership styles influence teacher performance. From a practical perspective, the study underscores the need for leadership development programs, targeted professional training, and policies that enhance teacher motivation and competence. Educational policymakers and school administrators should focus on fostering a positive work culture and implementing transformational leadership strategies to optimize teacher performance. Future research should explore additional contextual factors that may further refine these relationships in different educational settings.